Vietnamese Learners's Experience in Korean Cultural Education - Dương, Thị Thanh Phương (2024)
This study is to discuss the implications of cultural education in Korean language education by examining the current status of cultural education for learners majoring in overseas Korean through the case of D University in Vietnam. To this end, we will examine the current status of Korean language education and cultural subjects at University D, and collect and analyze data through in-depth interviews with learners. The in-depth interview target is 8 students who took Korean culture classes among Korean Studies students at D University. As a result of the study, first, it was found that learners recognized the importance of cultural understanding in the process of learning Korean. Second, 'cultural learning by experience', 'use of bilingual teaching and learning materials', and 'cultural teaching and learning through comparison with Vietnamese culture' were found to be desired by learners. Therefore, in order to maximize the efficiency of cultural education, a more systematic composition of educational content that reflects the needs of learners, and the manpower of instructors who match it must be adopted.